Customer’s acceptance towards internet banking in Maybank / Elena Sofia Mohammad @ Mokhtar - Mohammad @ Mokhtar, Elena Sofia (Faculty of Business and Management, 2014)
The Internet has emerged as one of the most important distribution channels for financial services firms. However, there is still a need to more fully understand the antecedents to customer use of banking via the Internet. The purpose of this study is to understanding the factors that affect the acceptance of internet banking towards Maybank’s customers. The findings found that performance expectancy, effort expectancy, social impact and anxiety are all significantly affecting the acceptance of the customers towards the internet banking. The findings also predict that predict 36.8 per cent of the variations internet banking acceptance. The acceptance led by the satisfaction among the customers itself, thus the dependent variable are measures based on the satisfaction acceptance where the highest mean is 4.02 where most of the respondents agree with the facilitating conditions to use internet banking is one of the factors that influenced the customer acceptance. Implications for banks are that they need to put much effort not only into making a user-friendly internet bank, but also into explaining to their customers how the internet bank is useful to them.